Projetos e grupos pesquisa na formação inicial: um estudo a partir das significações imaginárias - Souza, Edilson de (2008)
This research aimed at understanding social representations built by students of graduation courses in Special Education and Pedagogy, who have participated in projects and research groups at the Education Center in Federal University of Santa Maria. Our reflections pointed to the importance of research in Special Education and Pedagogy courses as a possibility of the beginners initial formation process construction that, in our viewpoint, has the participation in projects and research groups as a crucial activity in the High Education Institution. We believe that the students participation in these activities stimulate them to develop scientific works and then the formation of a future investigator or a more competent professional. The research aimed mainly at knowing Special Education and Pedagogy students representations about teachers initial formation and also to identify factors that influence in these students representations constructions related to the participation in projects and research groups and to understand Special Education and Pedagogy students formation processes constructions. In order to present our research intention, we tried to expose a little more about our understanding of research groups and its importance as well, and also about the investigation in education. We presented and discussed the theory formulated by Cornelius Castoriadis (1982, 1987, 1992, 1999) about the social imaginary dimensions both instituted and instituting, believing on the possibility of the social significations built by the subjects approximation throughout their formation process. In this way, the problem of this research is: what is the sense of the social representations attributed by Special Education and Pedagogy students to their formation considering their participation in projects and research groups? This proposal is based on a qualitative methodology and also on Bogdan Biklen s (1994) theoretical production, mainly related to the characteristics of this approach and related to the utilized data collection instruments. In this way, this investigation tries to understand UFSM Education Center students concepts of research that are built during their academic life. We observed that the sense built by the participants about self-formation is far away from a social transformation, but concerned only about their individual formation process and in qualifying themselves to dispute better conditions besides ascending socially, being these facts the instituted social representations.